I saw this and thought of you: Some social uses of camera phones - Kindberg, Tim; Spasojevic, Mirjana; Fleck, Rowanne; Sellen, Abigail (Proceedings of CHI 2005, 2005)
This paper presents aspects of a study into how and why people use camera phones. The study examined people's intentions at the time of image capture and subsequent patterns of use. Motivated by current interest in "picture messaging", we focus on images taken to communicate with absent people and look at how they were actually used. We consider the timeliness of communication and the role of common ground to derive implications for design.